2016
DOI: 10.1016/j.ecoser.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being indicators for large-scale assessment of cultural ecosystem services

Abstract: The substantial importance of cultural benefits as a source of human well-being is increasingly recognised in society-environment interactions. The integration of cultural ecosystem services (CES) into the ecosystem services framework remains a challenge due to the difficulties associated with defining, articulating and measuring CES. We operationalise a novel framework developed by the UK National Ecosystem Assessment that identifies CES as the interactions between environmental spaces (i.e. physical localiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 55 publications
4
103
0
2
Order By: Relevance
“…For example, diverse stakeholders expressed how important the sites were to their wellbeing, expressed a love of the sea and an appreciation of the beauty of sites, and shared a sense of belonging. (see Bryce et al, 2016;Kenter et al, 2016b in this issue for comparable findings with other marine users). One of the follow up interviewees, an environmentalist, reflected on the benefits of allowing a broader range of values to be considered in decision-making: "When we're talking about MPAs, a really substantial proportion of what they can actually deliver are social and environmental benefits which may also have some short term impacts on business …I think that methods like CVM go far beyond just simple economic decision-making tool and incorporate the views of people in a much more holistic way.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, diverse stakeholders expressed how important the sites were to their wellbeing, expressed a love of the sea and an appreciation of the beauty of sites, and shared a sense of belonging. (see Bryce et al, 2016;Kenter et al, 2016b in this issue for comparable findings with other marine users). One of the follow up interviewees, an environmentalist, reflected on the benefits of allowing a broader range of values to be considered in decision-making: "When we're talking about MPAs, a really substantial proportion of what they can actually deliver are social and environmental benefits which may also have some short term impacts on business …I think that methods like CVM go far beyond just simple economic decision-making tool and incorporate the views of people in a much more holistic way.…”
Section: Discussionsupporting
confidence: 69%
“…This study, which demonstrated an innovative approach integrating a film-based interpretive approach with a deliberative-democratic multicriteria evaluation, highlights the power of film-based interpretation in building trust between conflicting interests by highlighting shared transcendental values and enabling more equal representation and participation, helping to address some of the key challenges of deliberative methods. It also addresses some of the key emerging themes in the cultural ecosystem services literature around the importance of interpretation, creative approaches, relational values and identities in grounding interventions in people's connection to place (in this issue: Bryce et al, 2016;Cooper et al, 2016;Edwards et al, 2016;Fish et al, 2016aFish et al, , 2016bKenter, 2016b). Combined with a deliberative-democratic rather than arithmetic approach to MCA, this provides an effective template for participatory management of MPAs and Ecosystem Approaches to conservation management more broadly, to help ensure the effective conservation of biodiversity and ecosystem services in a way that is equitable, inclusive and effective.…”
Section: Discussionmentioning
confidence: 98%
“…Another way to approach the difficulties in assessing CES is by explicitly linking their benefits to the multiple dimensions of human wellbeing (Plieninger et al 2013, Busch et al 2011, Bryce et al 2016, Daw et al 2016. This is an underdeveloped research topic within marine and coastal CES.…”
Section: Synergies Trade-offs and Bundles Of Marine And Coastal Cesmentioning
confidence: 99%
“…Currently abroad, the issue of cultural ecosystem services provided by landscape and their valuation are intensively discussed in many scientifi c papers, e.g. Bryce et al (2016), Dickinson and Hobbs (2017), Lupp et al (2016), Rewitzer et al (2017, Small et al (2017) or Stalhammar and Peresen (2017). Tengberg et al (2012), andChan et al (2012) have proposed that methods of valuating cultural heritage and identity in landscape be integrated into ecosystem service valuation and thus help inform public policy-makers and urban designers in landscape and environmental management processes.…”
Section: Economic Value Of Ecosystem Services In An International Conmentioning
confidence: 99%